1936. Implementation of IV Push Antibiotics for OPAT in a Safety Net Hospital Following a National Fluid Shortage. (26th November 2018) - Bhavan, Kavita; Bird, Cylaina; Ganguly, Anisha; King, Helen; Schmalstieg, Aurelia; Mang, Norman; Ortwine, Jessica; Wei, Wenjing; Collins, Ryan
Abstract: Background: In the wake of Hurricane Maria, hospitals nationwide have faced a shortage of IV fluids sourced from Puerto Rico. Out of necessity to conserve IV fluids, Parkland Memorial Hospital shifted IV antibiotic administration from traditional fluid suspension via pump/gravity to "IV push" administration. The safety and potential cost savings of short infusion administration of antibiotics have been previously described; however, implementation of IV push administration among patients receiving long-term IV antibiotics has yet to be described. Methods: Starting November 2017, patients requiring long-term IV antimicrobial treatment with were transitioned to receive IV push administration from infusion. Per the Parkland self-administered Outpatient Parenteral Antimicrobial Therapy (S-OPAT), patients were screened and trained to self-administer IV antibiotics prior to hospital discharge and followed in the Parkland OPAT clinic. Results: Since implementation November 2017, 200 patients completed antimicrobial therapy with IV push method with 100% success rate and no reported complications. The following supplies were estimated to be saved: 3, 000 less IV fluid bags, 1, 000 IV tubing, and 50% fewer gloves and alcohol swabs, amounting to approximately 22, 000 of cost savings for a patient going home on once a day antibiotic therapy. Teaching time for the nursing team was reduced on average by 50% per patient. Preliminary patient satisfaction surveys indicate greater satisfaction due to decreased infusion time from an average of 45 minutes to 3–5 minutes with the IV push method. Patient's reported satisfaction with the new IV Push method due to greater convenience for both storing the medication and a faster preparation time. Conclusion: Parkland Memorial Hospital was able to implement IV push as a safe and cost-effective alternative to traditional IV antibiotic administration in fluid suspension. Use of IV push antibiotics resulted in 22, 000 of cost savings and reduced utilization of a critical resource currently facing a nationwide shortage. Though implemented at our institution in response to a national crisis, IV push is a favorable alternative to administration via a pump or gravity due to time savings, cost reduction, and convenience. Disclosures: All authors: No reported disclosures.